Geo-economic role of Ukraine's Foreign Trade and Mechanism of its Implementation in the Conditions of European Integration - Mytsenko, I.; Babets, I.; Mytsenko, V.; Sokolovska, O. (Polygraph-Service, 2025)
The monograph is dedicated to the study of the development challenges of Ukraine’s foreign trade within the framework of European integration processes. It highlights the essence, directions, and levels of foreign trade under conditions of geoeconomic change. The work defines general patterns of foreign economic activity and characterizes the genesis of the theoretical and methodological foundations of foreign trade in the context of global transformations. Монографію присвячено дослідженню проблем розвитку зовнішньої торгівлі України в євроінтеграційних процесах. Висвітлено сутність, напрями та рівні зовнішньої торгівлі в умовах геоекономічних змін. Визначено загальні закономірності зовнішньоекономічної діяльності та охарактеризовано генезис теоретико-методологічних засад зовнішньої торгівлі в контексті глобальних трансформацій.
Геоекономічна роль зовнішньої торгівлі України та механізм її реалізації в умовах європейської інтеграції
Keywords: foreign trade; European integration; foreign economic activity; зовнішня торгівля; євроінтеграційні процеси; зовнішньоекономічна діяльність